Model of innovative management activities of the head of an education institution - Shalimova, I.; Shalimova, A. (Problems of Engineer-Pedagogical Education, 2021)
Based on the theoretical analysis of psychological and pedagogical literature on the management of socio-pedagogical systems, innovation management, educational management, pedagogical management, pedagogical innovation, the article states that innovative processes ensure the development of education institutions and require innovative management as such, which contributes to the implementation of general innovation processes and the involvement of participants in the educational process. The article defines that the innovative management activities of the head of a general secondary education institution should be understood as a set of specific management principles, functions and technologies, which ensure the constant development of the education institution and increase its competitiveness. The article examines the advantages of education institutions operating in a competitive environment, namely the inclusion of education institutions in scientific management; application of innovations; constant monitoring and marketing; use of modern information and telecommunication technologies, experimental activity, implementation of co-management, development of responsibility for consequences of the taken decisions, administrative and pedagogical activity, creation of a system of high-quality personality-oriented education, improvement of the material and technical base. The article proves that as a result of the implementation of innovative management activities of the head of a general secondary education institution, the education institution acquires indicators of innovation and competitiveness. The authors of the article identify trends in the theory of management of general secondary education and management activities of its head in terms of educational innovations, namely drawing the attention of scientists to studying the features of management of education institutions of different types and forms of ownership in the market; comparing the theory of management of social systems with economic theories for the purpose of their approximation and adaptation; studying political, economic, social, pedagogical, psychological conditions for the application of innovations; studying ways of information and investment support of education institutions; developing diagnostic, evaluation and expert procedures in the management of education institutions.